ANALISIS DAMPAK EKONOMI DAN SOSIAL AKIBAT KEMACETAN LALU LINTAS DI JALAN RAYA BOGOR-JAKARTA - Sahniza Tamara; Hadi Sasana (Riset Ekonomi Pembangunan, 2017)
Traffic congestion can occur due to the imbalance between population growth, vehicles growth, and roads growth (Mustikarani, 2016). Population growth in Jakarta in the period 20102015 is 1.1% per year, vehicle growth in Jakarta is 8.75% per year, and road growth in Jakarta is 0.01% per year. The imbalance between population growth, vehicle growth, and road growth caused traffic congestion. One of the streets in Jakarta that is often struck by traffic congestion is Raya Bogor-Jakarta street. The purpose of this reasearch is to analyze the economic impacts social impacts felt by motorists due to traffic congestion on Raya Bogor-Jakarta street.  The method used to calculate and analyze economic impacts is a quantitative method of calculating the average, lost of earnings, and lost economic potential. While to analyze the social impact used qualitative analysis method. The results showed that the economic potential lost due to traffic congestion on Raya Bogor-Jakarta street reaches Rp 31.017.020.346 per year. The social impact of traffic congestion on Raya Bogor-Jakarta street was 89% of respondents felt tired, 91% of respondents felt upset, 49% of respondents felt stressed, and 96% of respondent felt uncomfortable.